The Relationship Between Islamic Dawah and The Concept of Islam Nusantara in A Multicultural Perspective - Hamid, Noor (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
This discussion elucidates that there is a polemic about the term concept of Islam Nusantara, and it turns out that in it there are multicultural values that provide a model strategy in doing da'wah, because the object has a multicultural or diverse background. This study has differences with some previous studies, because in this discussion the researcher relates to the relationship of Islamic Da'wah. Researcher employ qualitative research methods and a literature review to investigate this relationship. The purpose of this study is to explore the relationship between Islamic Da'wah with the concept of Islamic archipelago which is essentially complementary in building an inclusive and harmonious society, where diversity will be valued and respected. And the results of this study is, there is a relationship between Islamic Da'wah with the concept of Islam Nusantara, especially in a multicultural perspective, because if seen many of the preachers who have not understood about how the strategy in preaching in an environment that has a diverse culture, both in terms of language, region, tribal and other forms of diversity. And from the concept of Islam Nusantara, from the beginning of the early history of Islam into Indonesia, the walisongo have indirectly provided views related to strategies in carrying out da'wah on people in various cultures and regions. This has brought influence and knowledge for preachers, especially through the concept of the term Islam Nusantara, which is multicultural.